The Role of Data Governance in Enhancing Government Transparency and Accountability - Jeffriansyah Dwi Sahputra Amory (Technology and Society Perspectives (TACIT), 2026)
This study aims to analyze the role of data governance in enhancing government transparency and accountability, as well as to identify the factors that support its implementation. The research employs a literature review method with a qualitative approach and descriptive analysis. Data were collected from Google Scholar, ScienceDirect, and various documents published by international organizations and credible government institutions during the period 2017–2026. The initial search process yielded 60 articles and documents, which were subsequently screened based on relevance, quality, and alignment with the research objectives, resulting in 49 sources being included in the analysis. Data analysis was conducted through thematic categorization, identification of key concepts, comparison of research findings, and interpretation. The results indicate that data governance plays a significant role in improving data quality, strengthening public information disclosure, reducing information asymmetry, and supporting government oversight and accountability processes. The findings also reveal that the successful implementation of data governance is influenced by policy quality, human resource capacity, and the level of information system integration across government agencies